1990
DOI: 10.1073/pnas.87.22.8751
|View full text |Cite
|
Sign up to set email alerts
|

Allelic loss of chromosomes 16q and 10q in human prostate cancer.

Abstract: Recent advances in understanding the molecular genetics of common adult tumors have indicated that multiple genetic alterations including the activation of oncogenes and the inactivation of tumor suppressor genes are important in the pathogenesis of these tumors. Loss of heterozygosity is a hallmark of tumor suppressor gene inactivation and has been used to identify chromosomal regions that contain these genes. We have examined allelic loss in the most common tumor in men, prostate cancer. Twenty-eight prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
208
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(219 citation statements)
references
References 42 publications
10
208
0
1
Order By: Relevance
“…Little is known of the acquired genetic changes that drive these tumors through the various stages of carcinogenesis. The most consistent genetic alterations in adenocarcinoma of the prostate are loss of heterozygosity (LOH) involving chromosome arms 7q, 8p, 10q, 13q, 16q, 17q and 18q, pointing to the presence of tumor suppressor genes (TSGs) in these deleted regions and their involvement in prostate carcinogenesis (Zenklusen et al, 1994;Bova et al, 1993;Ittman, 1996;Cooney et al, 1996;Carter et al, 1990;Gao et al, 1995;Latil et al, 1994). The demonstration of LOH in certain chromosomes has potentially implicated previously identi®ed TSGs, incuding CDH1 on 16q (Umbas et al, 1992), and DCC on 18q (Gao et al, 1993), even though the precise role of these TSGs in prostate cancer is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Little is known of the acquired genetic changes that drive these tumors through the various stages of carcinogenesis. The most consistent genetic alterations in adenocarcinoma of the prostate are loss of heterozygosity (LOH) involving chromosome arms 7q, 8p, 10q, 13q, 16q, 17q and 18q, pointing to the presence of tumor suppressor genes (TSGs) in these deleted regions and their involvement in prostate carcinogenesis (Zenklusen et al, 1994;Bova et al, 1993;Ittman, 1996;Cooney et al, 1996;Carter et al, 1990;Gao et al, 1995;Latil et al, 1994). The demonstration of LOH in certain chromosomes has potentially implicated previously identi®ed TSGs, incuding CDH1 on 16q (Umbas et al, 1992), and DCC on 18q (Gao et al, 1993), even though the precise role of these TSGs in prostate cancer is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…In another study the most frequent locus (53%) altered by MSI was 10q23-24, 291 which is a common site of allelic loss in PC. 175 The frequency of MSI in latent cancer is lower than in clinical PC. 292 …”
Section: Mismatch Repair Genesmentioning
confidence: 99%
“…There are frequent deletions in the region of chromosome 16q where the E-cadherin gene is located. 175,176 Loss of E-cadherin function has been implicated in the pathogenesis of sporadic colorectal and other cancers. 177 Patients with germline mutation in the Ecadherin gene face a 70-80% likelihood of developing familial gastric cancer during their lifetime.…”
Section: Epithelial-cadherin Tsgmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23] The sites most frequently lost in somatic cancers include 8p, 10q, 13q, 16q and 18q, [11][12][13]15,20,22,23 and losses on 1q are associated with hereditary prostate cancer. 19 Some losses, such as those on 8p and 13q, are associated with early prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…19 Some losses, such as those on 8p and 13q, are associated with early prostate cancer. 11,12,22,23 Others, such as those on 11p and 16q, 15,[20][21][22]24 are more frequent in advanced disease. Several studies have reported an association of AI at certain loci with histopathological features of the RP specimen, including advanced stage, 13,[25][26][27] high Gleason grade 13,26 and perineural invasion.…”
Section: Introductionmentioning
confidence: 99%